2010
DOI: 10.1371/journal.pone.0012800
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Quantification of Vcam-1 Expression in Renal Ischemia Reperfusion Injury Using Non-Invasive Magnetic Resonance Molecular Imaging

Abstract: Rationale and ObjectiveVascular cell adhesion molecule-1 (VCAM-1) is upregulated in ischemia reperfusion injury (IRI), persisting after restoration of blood flow. We hypothesized that microparticles of iron oxide targeting VCAM-1 (VCAM-MPIO) would depict “ischemic memory” and enable in vivo assessment of VCAM-1 expression.Methodology and FindingsMice subject to unilateral, transient (30 minutes) renal ischemia and subsequent reperfusion received intravenous VCAM-MPIO (4.5 mg iron/kg body weight). Contrast agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 37 publications
1
46
0
1
Order By: Relevance
“…At the same time, considerably greater numbers of USPIO/SPIO are required to achieve the same contrast effect as for MPIO because of the markedly lower iron content and greatly reduced targeting valency of each particle [USPIO = 2.4-24 antibodies per particle (43) vs. VCAM-MPIO ∼ 25,000 antibodies per particle]. To date, no adverse events with the nonbiodegradable VCAM-MPIO have been observed in mice over 72 h after administration, and we have previously reported that, at both 30 min and 24 h after administration, antibody-conjugated 1-μm MPIO accumulate predominantly in the spleen and liver (24,44). We have now also assessed the possibility of systemic macrophage activation at the molecular level as a consequence of VCAM-MPIO administration, and we have found that an antiinflammatory rather than proinflammatory phenotype is induced in the liver (SI Text 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, considerably greater numbers of USPIO/SPIO are required to achieve the same contrast effect as for MPIO because of the markedly lower iron content and greatly reduced targeting valency of each particle [USPIO = 2.4-24 antibodies per particle (43) vs. VCAM-MPIO ∼ 25,000 antibodies per particle]. To date, no adverse events with the nonbiodegradable VCAM-MPIO have been observed in mice over 72 h after administration, and we have previously reported that, at both 30 min and 24 h after administration, antibody-conjugated 1-μm MPIO accumulate predominantly in the spleen and liver (24,44). We have now also assessed the possibility of systemic macrophage activation at the molecular level as a consequence of VCAM-MPIO administration, and we have found that an antiinflammatory rather than proinflammatory phenotype is induced in the liver (SI Text 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This property has previously been used to track MPIO-labeled tumor cells in mouse models, thus enabling visualization of early metastasis distribution in the brain with sensitivity down to a single metastatic cell loaded with ∼50 pg iron at an imaging field strength of 1.5 T (17). Alternatively, conjugation of MPIO with targeting ligands enables their accumulation at sites where specific molecules are expressed (18)(19)(20)(21)(22)(23)(24)(25). Importantly, the targeted MPIO are not taken up by endothelial cells and do not enter the brain, thus providing an endovascular biomarker for pathology within the brain.…”
mentioning
confidence: 99%
“…For example, quantitative molecular imaging has been described for VCAM1 and P-selectin using 'leukocyte-mimetic' particles to examine extent and distribution of endothelial activation 102,103 , which has also been applied to measure the 'imprint' of previous ischaemia 104 . An alternative approach has been to image proteases that are critical in the pathogenesis of disease and has been applied to preclinical models 105 and humans after AMI 100 .…”
Section: Targeting Of Biological Processesmentioning
confidence: 99%
“…Substantially, the most relevant implications of integrins in pathology and therapy, already focused in therapeutic and diagnostic approaches [27][28][29], and currently also in the development of targeted NPs (although still limited to preclinical investigations) [30][31][32] are amenable to the role played by integrin α v β 3 in cancer angiogenesis [33][34][35], in cancer cell proliferation and metastatic diffusion [36][37][38][39], in angiogenesis in ischemic tissues, in atherosclerotic damage [29,40,41] and in vascular restenosis [42], as well as in osteoporosis [43], by integrin α 5 β 1 in angiogenetic processes [33,34,44], by integrin α IIb β 3 , mediating adhesion of platelets to fibrinogen, in thrombotic conditions [45,46], and by the leukocyte integrins α 4 β 1 , α 4 β 7 , α L β 2 and α M β 2 in inflammatory conditions and autoimmune diseases affecting various systems, e.g., multiple sclerosis, ulcerative colitis and Crohn's disease, asthma, psoriasis [29,[47][48][49], and in any way involving the adhesion and transmigrations of leukocytes across the vascular endothelium [50][51][52][53].…”
Section: Integrins In Diseasesmentioning
confidence: 99%
“…Up to now, the feasibility of targeting VCAM-1 with NPs has been explored only with antibodies, in vivo in atherosclerotic mice, and in murine models of renal and cerebral ischemia [52,53,256,264,266]. It can be noted that in the McAteer study [265], a particle dually labelled with P-selectin and VCAM-1 antibodies was also investigated.…”
Section: Leukocyte Integrinsmentioning
confidence: 99%